Novel Alleles of Two Tightly Linked Genes Encoding Polygalacturonase-Inhibiting Proteins (VrPGIP1 and VrPGIP2) Associated with the Br Locus That Confer Bruchid (Callosobruchus spp.) Resistance to Mungbean (Vigna radiata) Accession V2709 - Kaewwongwal, Anochar; Chen, Jingbin; Somta, Prakit; Kongjaimun, Alisa; Yimram, Tarika; Chen, Xin; Srinives, Peerasak (Frontiers in Plant Science, 2017)
Nearly all mungbean cultivars are completely susceptible to seed bruchids (Callosobruchus chinensis and Callosobruchus maculatus). Breeding bruchid-resistant mungbean is a major goal in mungbean breeding programs. Recently, we demonstrated in mungbean (Vigna radiata) accession V2802 that VrPGIP2, which encodes a polygalacturonase inhibiting protein (PGIP), is the Br locus responsible for resistance to C. chinensis and C. maculatus. In this study, mapping in mungbean accession V2709 using a BC11F2 population of 355 individuals revealed that a single major quantitative trait locus, which controlled resistance to both C. chinensis and C. maculatus, was located in a 237.35 Kb region of mungbean chromosome 5 that contained 10 annotated genes, including VrPGIP1 (LOC106760236) and VrPGIP2 (LOC106760237). VrPGIP1 and VrPGIP2 are located next to each other and are only 27.56 Kb apart. Sequencing VrPGIP1 and VrPGIP2 in ‘V2709’ revealed new alleles for both VrPGIP1 and VrPGIP2, named VrPGIP1-1 and VrPGIP2-2, respectively. VrPGIP2-2 has one single nucleotide polymorphism (SNP) at position 554 of wild type VrPGIP2. This SNP is a guanine to cystine substitution and causes a proline to arginine change at residue 185 in the VrPGIP2 of ‘V2709’. The VrPGIP2 allele in ‘V2709’ was designated as VrPGIP2-2. VrPGIP1-1 has 43 SNPs compared with wild type and ‘V2802’, and 20 cause amino acid changes in VrPGIP1. One change is threonine to proline at residue 185 in VrPGIP1, which is the same as in VrPGIP2. Sequence alignments of VrPGIP2 and VrPGIP1 from ‘V2709’ with common bean (Phaseolus vulgaris) PGIP2 revealed that residue 185 in VrPGIP2 and VrPGIP1 contributes to the secondary structures of proteins that affect interactions between PGIP and polygalacturonase, and that some amino acid changes in VrPGIP1 also affect interactions between PGIP and polygalacturonase. Thus, tightly linked VrPGIP1 and VrPGIP2 are the likely genes at the Br locus that confer bruchid resistance in mungbean ‘V2709’.